Spinopelvic sagittal alignment of patients with transfemoral amputation - Facione, Julia; Villa, Coralie; Bonnet, Xavier; Barrey, Cédric; Thomas-Pohl, Marie; Lapeyre, Eric; Lavaste, François; Pillet, Hélène; Skalli, Wafa (European spine journal, 2019)
Purpose This study aims to describe the spinopelvic sagittal alignment in transfemoral amputees (TFAs) from a radiologic study of the spine with a postural approach to better understand the high prevalence of low back pain (LBP) in this population. Methods TFAs underwent X-rays with 3-D reconstructions of the full spine and pelvis. Sagittal parameters were analyzed and compared to the literature. Differences between TFAs with and without LBP were also observed. Results Twelve subjects have been prospectively included (TFA-LBP group ( n = 5) and TFA-NoP group ( n = 7)). Four of the five subjects of the TFA-LBP group and two of the seven in TFAs-NoP group had an imbalanced sagittal posture, especially regarding the T9-tilt, significantly higher in the TFA-LBP group than in the TFA-NoP ( p = 0.046). Eight subjects (6 TFA-NoP and 2 TFA-LBP) had abnormal low value of thoracic kyphosis (TK). Moreover, the mean angle of TK in the TFA-NoP group was lower than in the TFA-LBP group ( p = 0.0511). Conclusion In the considered sample, TFAs often present a sagittal imbalance. A low TK angle seems to be associated with the absence of LBP. It can be hypothesized that this compensatory mechanism of the sagittal imbalance is the most accessible in this population. This study emphasizes the importance of considering the sagittal balance of the pelvis and the spine in patients with a TFA to better understand the high prevalence of LBP in this population. It should be completed by the analysis of the spinopelvic balance and the lower limbs in 3D. Graphical abstract These slides can be retrieved under Electronic Supplementary Material.